Long-term outcomes of bovine pericardial patch angioplasty for recurrent stenosis in vascular access: A UK single-centre experience. Issue 6 (November 2018) - Fisher, Owain; Meecham, Lewis; Buxton, Pauline; Legge, Jocelyn; Fairhead, Jack; Rajagopalan, Sriram; Asquith, John; Pherwani, Arun
Introduction: Stenosis of an arteriovenous fistula or arteriovenous graft for dialysis is a common problem. Stenosis may lead to a number of problems including failure of the fistula. Treatment of stenosis is commonly with percutaneous angioplasty or surgical patch angioplasty with autologous vein or synthetic graft or patch. Here we report the use of bovine pericardial patch angioplasty as an alternative mode of patch angioplasty when percutaneous intervention has failed. Methods: Patients with fistulae treated with bovine patch angioplasty between 2013 and 2016 were identified from a prospectively maintained renal access database (Cyberren ® ). Patient records were reviewed, noting type and location of access, patency, re-interventions and complications post bovine pericardial patch. Results: A total of 40 patients were identified as having undergone bovine pericardial patch angioplasty between January 2013 and April 2016. The median time from fistula formation to bovine pericardial patch was 15 months (interquartile range (IQR): 5–43). Median duration of follow-up was 14 months (IQR: 5–18). Primary patency at 6, 12, 18 and 24 months was 91%, 66%, 61% and 54%, respectively. Secondary patency was 94%, 91%, 80% and 77% at the same time points, respectively. In total, 15 patients required 23 re-interventions post bovine pericardial patch. There has been no report of infection or aneurysm formation. Conclusion: Bovine pericardial patch angioplasty for recurrent stenosis in arteriovenous fistulae for dialysis access provides a robust alternative to other surgical patches with the added advantage of allowing early needling and relative resistance to infection. Rates of restenosis and failure post bovine pericardial patch are low.